Macrophages Inhibit Ciliary Protein Levels by Secreting BMP-2 Leading to Airway Epithelial Remodeling Under Cigarette Smoke Exposure - Wang, Zhigang; Liang, Wenzhang; Ma, Cuiqing; Wang, Jiachao; Gao, Xue; Wei, Lin (Frontiers in Molecular Biosciences, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease with high morbidity and mortality worldwide. So far, smoking is still its leading cause. The characteristics of COPD are emphysema and airway remodeling, as well as chronic inflammation which was predominated by macrophages. Some studies have reported that macrophages were involved in emphysema and chronic inflammation, but whether there is a link between airway remodeling and macrophages remains unclear. Here, we found that acute and chronic cigarette smoke exposure both led to increase of macrophages in the lung and decrease of ciliated cells in the airway epithelium in mouse model. The results of in vitro experiments showed that the ciliary protein (β-tubulin-Ⅳ) expression of BEAS-2B cells could be inhibited when co-cultured with human macrophage line THP-1, and the inhibitory effect was augmented with the stimulation of cigarette smoke extract (CSE). Based on the results of transcriptome sequencing, we focused on the protein, BMP-2, secreted by macrophage, that might mediate this inhibitory effect. Further studies confirmed that BMP-2 protein inhibited β-tubulin-Ⅳ expression of BEAS-2B cells under the stimulation of CSE. Coincidentally, this inhibitory effect could be nearly blocked by BMP receptor inhibitor LDN or be interfered with BMP-2 siRNA. This study suggests that activation and infiltration of macrophages in the lung induced by smoke exposure lead to BMP-2 high expression, which in turn inhibits ciliary protein expression of bronchial epithelial cells, contributing to the remodeling of airway epithelium and aggravate the development of COPD.